ESTUDIO DE LOS FORAMINÍFEROS DE LA FORMACIÓN PIRABAS (MIOCENO INFERIOR), ESTADO DE PARÁ, BRASIL Y SU CORRELACIÓN CON FAUNAS DEL CARIBE - de Araújo Távora, Vladimir (2011)
Vertical variation in the foraminifera content detected by quantitative and qualitative studiespermitted recognition of eight biofacies along the Pirabas Formation at the investigated area. The assemblagesare related to shallow shelf and marginal marine paleoenvironments. Cyclical fluctuations in the marginalmarine environments demonstrated changes in the water‘s depth and salinity.The presence of planktonic foraminifera confirms the Early Miocene age for the Pirabas Formation. Thepresence of Globorotalia kugleri Bolli and Globigerinoides primordius Blow & Banner at the base, andGlobigerinoides altiaperturus Bolli and Globigerinoides trilobus trilobus (Reuss) at the top of outcrop permitcorrelation to N4 and N5 International Biostratigraphic Zones of Blow (1969).